Governança das águas no Brasil: colaborações da sociedade civil e desafios da implementação do Sistema Nacional de Gerenciamento de Recursos Hídricos - Marcon, Priscila (2023)
The Brazilian hydric scenario is complex, requiring management and governance practices to respond to current demands while preparing for future challenges. Federal Law No. 9433, enacted in 1997, established a way of managing water in Brazil based on the integration among sectors, participation of different actors, and on decentralized decision-making processes. This law also determined a set of institutions responsible for its implementation, composed of federal, state, district, and river basin levels entities, which is called the National Water Resources Management System (NWRMS). However, part of the existing difficulties in implementing these molds of water management may be since that NWRMS is not consolidated yet and these institutions have found obstacles to acting according to their responsibilities. Thus, this research objective was to identify and analyze the gaps, difficulties, and challenges that the NWRMS bodies have been facing, to investigate possible civil society synergies, and collaborations in water management and governance. These limitations identification were possible with a Systematic Review of the literature combined with the Content Analysis. To consider the importance of social actors involved in water management and governance, even if they do not participate in an institutionalized way in NWRMS, semi-structured interviews were carried out with representatives of movements, initiatives, and civil society organizations, whose responses were also examined with the Content Analysis use. The results indicate that there are a series of structural aspects, disputes, and interconnected operational constraints that hinder the promotion of integrated, decentralized and participatory water management. It was also noted that the civil society entities that are active in water governance have aligned perceptions about the limitations of NWRMS with the aspects found in the specialized literature. In addition, it was observed that the performance of entities, such as those interviewed, despite the latent potential, has contributed indirectly to the functioning of NWRMS. Within the analyzed context, it is pointed out that the main synergies brought by initiatives, movements, and civil society organizations are found in water governance, in which they have acted to sustain accomplished practices, claim improvements, and resist setbacks in water management. Finally, it reflects on water governance based on the Complex Adaptive Systems approach, a theoretical framework that supported the understanding, systematization and integration of the reflections arising from the analysis carried out in this work.